Coretax Implementation Model On The Quality Of Individual Taxpayer Reports - Aris Munandar; lesi Hertati; Fadila Febrianti (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Coretax, as a technology-based tax administration system, can improve the accuracy, transparency, and timeliness of tax reporting. This study aims to analyze the Coretax implementation model on the quality of individual taxpayer reports in the era of digital tax administration. The research used a quantitative approach, with data collected through questionnaires distributed to 37 individual taxpayers, including elementary, middle, and high school teachers at Indo Global Mandiri who have used the Coretax system. Data analysis was conducted using simple linear regression to test the effect of independent variables on the dependent variable. The results showed that Coretax implementation had a positive and significant impact on the quality of individual taxpayer reports. This was demonstrated by increased compliance rates, reduced reporting errors, and ease of the tax administration process. Coretax implementation can be an effective solution to improve the quality of tax reporting in Indonesia and support the optimization of the national tax system.